Effects of scientific policies in the Spanish university : research projects in English language and Linguistics = Repercusión de la política científica en la Universidad Española ; proyectos de investigación en Lengua y Lingüística Inglesa - Fernández Bajón, María Teresa
We briefly explore the relationships between scientific and educational policies and the Spanish university system, and try to identify some converging themes in these fields and some future directions for the improvement of the scientific research done at tertiary level. This article also offers a general view of the different funded research projects in English language and linguistics carried out by Spanish university groups with the aim of reporting on the trends and interests.